Characterization of pomegranate peel extract loaded nanophytosomes and the enhancement of bio-accessibility and storage stability - Dundar, Ayse Neslihan; Ozdemir, Sebahat; Uzuner, Kubra; Parlak, Mahmud Ekrem; Sahin, Oya Irmak; Dagdelen, Adnan Fatih; Saricaoglu, Furkan Turker (Elsevier Sci Ltd, 2023)
Nano-phytosomes are lipid-based nano-carriers and rapidly growing technology for products containing phytochemicals. In this study, pomegranate peel extract (PPE) loaded nanophytosomes (NP) were prepared with phosphatidylcholine (PC) based on thin layer hydration method. The characterization of NP such as entrapment efficiency (EE), particle size, poly-dispersity index (PDI),.-potential and microstructural properties was studied and in vitro bioaccessibility and storage stability of bioactive properties were investigated. The highest EE was determined as 94.99 %, indicating a unique ability as nano-carrier. PPE-loaded NPs showed good characteristics, such as lower PDI values (<0.5), lower particle size (166.70-144.40 nm), and spherical shape of microstructure. All NP complexes showed significant bioaccessibility with TPC, CUPRAC, and ABTS values >50 % in the intestinal medium. The lowest TPC and color difference (.E) during 28 days of storage were found at 4.C, although all NP samples showed better stability at all storage temperatures up to 21 days.
Keywords: Pomegranate by-products; Nanophytosome; In vitro digestion; Nanoencapsulation